Exposure of human intestinal epithelial cells and primary human hepatocytes to trypsin-like serine protease inhibitors with potential antiviral effect - Pászti-Gere, Erzsébet (J Enzyme Inhib Med Chem, 2021)
Human intestinal epithelial cell line-6 (HIEC-6) cells and primary human hepatocytes (PHHs) were treated with 3-amidinophenylalanine-derived inhibitors of trypsin-like serine proteases for 24 hours. It was proven that treatment with MI-1900 and MI-1907 was tolerated up to 50 μM in HIEC-6. These inhibitors did not cause elevations in extracellular H(2)O(2) levels and in the concentrations of interleukin (IL)-6 and IL-8 and did not alter occludin distribution in HIEC-6. It was also found that MI-1900 and MI-1907 up to 50 μM did not affect cell viability, IL-6 and IL-8 and occludin levels of PHH. Based on our findings, these inhibitors could be safely applicable at 50 μM in HIEC-6 and in PHH; however, redox status was disturbed in case of PHH. Moreover, it has recently been demonstrated that MI-1900 prevents the replication and spread of the new SARS-CoV-2 in infected Calu-3 cells, most-likely via an inhibition of the membrane-bound host protease TMPRSS2.